Sistem Monitoring Kinerja Karyawan Berbasis Website Dengan Framework SCRUM Pada Penjualan Software ODOO - Palandeng, Rico Ismail; Retnoningsih, Endang (Journal of Students‘ Research in Computer Science, 2021)
The use of technology in companies can encourage performance and ease in evaluating employee performance. The performance monitoring mechanism that still uses a manual system, usually the HRD section receives the progress of the employee's work based on the recording in a spreadsheet such as excell. An excel file containing job updates for each employee becomes a reference as a monitoring parameter for employee work. This makes the work difficult to monitor so that HRD and Directors can find it difficult to assess employee performance. The development of the selected monitoring system is based on the website. With a website-based system, it can make the monitoring process effective and efficient because each employee can directly enter the work process he does directly into the system, and the HRD department can monitor the completion of employee work in real time, thus the Director can assess employee performance more objectively. and with the system as well as the performance monitoring report produced, it can minimize human errors.